Clinical outcomes of bronchiectasis in India: data from the EMBARC/Respiratory Research Network of India registry. Issue 1 (5th January 2023) - Dhar, Raja; Singh, Sheetu; Talwar, Deepak; Murali Mohan, B.V.; Tripathi, Surya Kant; Swarnakar, Rajesh; Trivedi, Sonali; Rajagopala, Srinivas; D'Souza, George; Padmanabhan, Arjun; Archana, B.; Mahesh, P.A.; et al.
Background: Identifying risk factors for poor outcomes can help with risk stratification and targeting of treatment. Risk factors for mortality and exacerbations have been identified in bronchiectasis but have been almost exclusively studied in European and North American populations. This study investigated the risk factors for poor outcome in a large population of bronchiectasis patients enrolled in India. Methods: The European Multicentre Bronchiectasis Audit and Research Collaboration (EMBARC) and Respiratory Research Network of India (EMBARC-India) registry is a prospective observational study of adults with computed tomography-confirmed bronchiectasis enrolled at 31 sites across India. Baseline characteristics of patients were used to investigate associations with key clinical outcomes: mortality, severe exacerbations requiring hospital admission, overall exacerbation frequency and decline in forced expiratory volume in 1 s. Results: 1018 patients with at least 12-month follow-up data were enrolled in the follow-up study. Frequent exacerbations (≥3 per year) at baseline were associated with an increased risk of mortality (hazard ratio (HR) 3.23, 95% CI 1.39–7.50), severe exacerbations (HR 2.71, 95% CI 1.92–3.83), future exacerbations (incidence rate ratio (IRR) 3.08, 95% CI 2.36–4.01) and lung function decline. Coexisting COPD, dyspnoea and current cigarette smoking were similarly associated with a worse outcome across all end-points studied. Additional predictors of mortality and severe exacerbations were increasing age and cardiovascular comorbidity. Infection with Gram-negative pathogens (predominantly Klebsiella pneumoniae ) was independently associated with increased mortality (HR 3.13, 95% CI 1.62–6.06), while Pseudomonas aeruginosa infection was associated with severe exacerbations (HR 1.41, 95% CI 1.01–1.97) and overall exacerbation rate (IRR 1.47, 95% CI 1.13–1.91). Conclusions: This study identifies risk factors for morbidity and mortality among bronchiectasis patients in India. Identification of these risk factors may support treatment approaches optimised to an Asian setting. Long-term follow-up of patients in the Indian Bronchiectasis Registry identifies independent predictors of poor outcome including frequent exacerbations and chronic infection with Gram-negative pathogens such as Klebsiella pneumoniae https://bit.ly/3cWh1u7